In-vivo Activity of IFN-λ and IFN-α Against Bovine-Viral-Diarrhea Virus in a Mouse Model - Quintana, María Eugenia; Barone, Lucas José; Trotta, Myrian Vanesa; Turco, Cecilia; Mansilla, Florencia Celeste; Capozzo, Alejandra Victoria; Cardoso, Nancy Patricia (Frontiers in Veterinary Science, 2020)
Bovine-viral-diarrhea virus (BVDV) can cause significant economic losses in livestock. The disease is controlled with vaccination and bovines are susceptible until vaccine immunity develops and may remain vulnerable if a persistently infected animal is left on the farm; therefore, an antiviral agent that reduces virus infectivity can be a useful tool in control programs. Although many compounds with promising in-vitro efficacy have been identified, the lack of laboratory-animal models limited their potential for further clinical development. Recently, we described the activity of type I and III interferons, IFN-α and IFN-λ respectively, against several BVDV strains in-vitro. In this study, we analyzed the in-vivo efficacy of both IFNs using a BALB/c-mouse model. Mice infected with two type-2 BVDV field strains developed a viremia with different kinetics, depending on the infecting strain's virulence, that persisted for 56 days post-infection (dpi). Mice infected with the low-virulence strain elicited high systemic TNF-α levels at 2 dpi. IFNs were first applied subcutaneously one day before or after infection. The two IFNs reduced viremia with different kinetics, depending on whether either one was applied before or after infection. In a second experiment, we increased the number of applications of both IFNs. All the treatments reduced viremia compared to untreated mice. The application of IFN-λ pre- and post-infection reduced viremia over time. This study is the first proof of the concept of the antiviral potency of IFN-λ against BVDV in-vivo, thus encouraging further trails for a potential use of this cytokine in cattle.